2007
DOI: 10.1002/esp.1530
|View full text |Cite
|
Sign up to set email alerts
|

Modified MMF (Morgan–Morgan–Finney) model for evaluating effects of crops and vegetation cover on soil erosion

Abstract: Modifications are made to the revised Morgan-Morgan-Finney erosion prediction model to enable the effects of vegetation cover to be expressed through measurable plant parameters. Given the potential role of vegetation in controlling water pollution by trapping clay particles in the landscape, changes are also made to the way the model deals with sediment deposition and to allow the model to incorporate particle-size selectivity in the processes of erosion, transport and deposition. Vegetation effects are descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
184
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(201 citation statements)
references
References 33 publications
7
184
0
2
Order By: Relevance
“…The guide values for detachability of clay, silt, and sand are 0.1, 0.5, and 0.3, respectively [27] but these values should be used carefully according to the soil characteristics of study sites as shown in Poesen [46] and it is recommended that users employ field-measured values.…”
Section: Sediment Delivery To Surface Runoffmentioning
confidence: 99%
See 2 more Smart Citations
“…The guide values for detachability of clay, silt, and sand are 0.1, 0.5, and 0.3, respectively [27] but these values should be used carefully according to the soil characteristics of study sites as shown in Poesen [46] and it is recommended that users employ field-measured values.…”
Section: Sediment Delivery To Surface Runoffmentioning
confidence: 99%
“…The guide values for detachability of clay, silt, and sand are 1.0, 1.6, and 1.5, respectively [27]. The values should be used carefully and can be replaced with observed site specific data.…”
Section: Sediment Delivery To Surface Runoffmentioning
confidence: 99%
See 1 more Smart Citation
“…We have applied the revised Morgan Morgan Finney model (RMMF) to estimate annual overland flow and its annual detachment rate and transport capacity [36][37][38] . The critical values of parameter are collected from table values of RMMF model 37 .…”
mentioning
confidence: 99%
“…The performance of the model is validated by the value of efficiency coefficient (EC) 40 and is applied successfully in the soil erosion research 38,41 .…”
mentioning
confidence: 99%